Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1016/j.jbusres.2020.10.032
|View full text |Cite
|
Sign up to set email alerts
|

How consumer confidence affects price conscious behavior: The roles of financial vulnerability and locus of control

Abstract: Highlights We aim to reconcile debate about the usefulness of consumer confidence (CC) indices. Contrary to prior research, we show that CC is not a singular construct. National CC affects price consciousness via personal CC and financial vulnerability. Locus of control moderates the effect of national CC on financial vulnerability. Implications relate to forecastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 57 publications
0
37
0
Order By: Relevance
“…In this case, they will have a negative external LOC during the journey by spreading negative WOM (Jiang et al, 2020). In contrast, tourists with a high internal LOC are less likely to be influenced by negative ascription during the journey (Hampson et al, 2021).…”
Section: Third Themes: Experience and Tourists' Characters As Locus Of Control Consequencesmentioning
confidence: 97%
See 2 more Smart Citations
“…In this case, they will have a negative external LOC during the journey by spreading negative WOM (Jiang et al, 2020). In contrast, tourists with a high internal LOC are less likely to be influenced by negative ascription during the journey (Hampson et al, 2021).…”
Section: Third Themes: Experience and Tourists' Characters As Locus Of Control Consequencesmentioning
confidence: 97%
“…luck, weather and fate). Secondly, powerful control whereby people can influence it (Hampson et al, 2021).…”
Section: Locus Of Control Typesmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-standard approach by B. Giovanni, M. Paolo [5] revealed chaos control with reference to the speculative bubbles, which can be managed by means of the control policies algorithm for chaotic dynamics. Hampson P. Daniel and G. Shiyang, X. Yi [6] referring to attribution theory stated that the external locus of control enhances the influence of consumers' trust in the country. Chinese researchers Li Yuanhui, Li Xiao, X. Erwei, H G. Dadrian [7] found that financial complications affect the selection of the profit management methods and determine the quality of internal control.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are two types of individuals' LOC; the first one is internal LOC, or, in another term (an internal attribution), which considers that individuals attribute events outcome to themselves than others [Jackson, 2019;Dunn, Jensen, Ralston, 2021]. In contrast, the external LOC or, in another term (an external attribution) considers that individuals attribute events outcome to external causes than themselves such as service providers' inefficiency or luck [Hampson, Gong, Xie, 2021].…”
Section: Theoretical Frameworkmentioning
confidence: 99%